2016
DOI: 10.1016/j.jsat.2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Examining Longitudinal Stimulant Use and Treatment Attendance as Parallel Outcomes in Two Contingency Management Randomized Clinical Trials

Abstract: The primary aim of this study was to examine stimulant use and longitudinal treatment attendance in one ‘parallel outcomes’ model in order to determine how these two outcomes are related to one another during treatment, and to quantify how the intervention impacts these two on- and off-target outcomes differently. Data came from two multi-site randomized clinical trials (RCTs) of contingency management (CM) that targeted stimulant use. We used parallel multilevel modeling to examine the impact of multiple pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Overall, our off-target findings of CM are consistent and of moderate size, which is consistent with other reports of off-target effects of CM. (McDonell et al, 2014; McDonell et al., 2013; McPherson et al, 2016) Moreover, the tobacco smoking outcomes observed in this preliminary study warrant further investigation. Development of novel behavioral and pharmacotherapeutic treatments that support patients with concurrent addiction to nicotine and MA is key given the high prevalence rates.…”
Section: Discussionmentioning
confidence: 73%
“…Overall, our off-target findings of CM are consistent and of moderate size, which is consistent with other reports of off-target effects of CM. (McDonell et al, 2014; McDonell et al., 2013; McPherson et al, 2016) Moreover, the tobacco smoking outcomes observed in this preliminary study warrant further investigation. Development of novel behavioral and pharmacotherapeutic treatments that support patients with concurrent addiction to nicotine and MA is key given the high prevalence rates.…”
Section: Discussionmentioning
confidence: 73%
“…A second limitation may be the lack of variability in a number of individual variables, particularly stimulant use. Despite recruiting clients in a residential treatment setting, drug use, as determined by the ASI drug subscale score, was nearly half that observed in previous studies with stimulant users (McPherson et al, 2016). Similarly, our population of stimulant users reported a relatively low number of physical illnesses or medical conditions (de la Cruz et al, 2016).…”
Section: Discussionmentioning
confidence: 77%
“… 6 It has also been demonstrated that CM indirectly reinforces treatment attendance when attendance is mandatory in order to provide the required urine sample. 65 While these off-target effects are modest and likely insufficient to be considered adequate treatment options on their own, these preliminary findings offer promising pathways for additional development. We discuss this further in our conclusions at the end of this review.…”
Section: Resultsmentioning
confidence: 96%